Modelling and Simulation of Photovoltaic-Variable Speed Diesel Generator Hybrid Power System for Off-Grid Rural Electrification - Lim, Pei; Nayar, Chemmangot (World Academic Publication Limited, 2012)
This paper presents the modelling and simulation of a Photovoltaic-Variable Speed Diesel Generator (PV-VSDG) Off-Grid hybrid power system for long term analytical performance studies. Two different types of diesel generators, namely the constant speed diesel generators (CSDG) and the VSDGs were considered for the simulations. The system components have been developed using MATLAB/Simulink. The simulation results from Simulink were validated through comparison to the results obtained from the Hybrid Optimisation Model for Electric Renewable (HOMER) simulation software. Simulink models were then used to evaluate the performance of all system configurations. Based on the analysis, it was found that systems using VSDGs perform better than those with conventional CSDGs. The developed models can be modified and used to study the systems’ performances using different power management strategies.